Extração, caracterização e modificação química da goma da anadenanthera macrocarpa - Leal, Maria Carolina Bezerra Di Medeiros (2014)
The objective of this study was to modify gum of Anadenanthera macrocarpa exudate by acetylation treatment and to evaluate its biotechnological potential as adhesive. The acetylation process was carried out under mild conditions, using acetic acid. Acetylation process of Pegico displaces pI and increases its thermal stability. The polysaccharide modification was characterized by the appearance of a new peak around 1542 cm-1 in the FTIR analysis, and in a crystalline structure characterized by sharp diffraction peaks at 14.9°, 16.8°, 17.8° and 22.5°. The acetylation also increased the swelling power of Pegicoac and reduced its solubility. Furthermore, acetylation treatment of Pegico produced higher adhesion strength in all tests conducted, characterized by an improvement in the adhesion strength in the 180° peeling test (0.205 to 0.288 N mm-1 ), in the T-peel test (0.044 to 0.088 N mm-1 ) and in the tensile bond test (0.088 to 0.133 N mm-2 ).